From the Red River to the Yellow River - Livdahl, David A. (Columbia Journal of Asian Law, 2013)
A Note Regarding This Article and the Author Readers should note that this article is not a traditional academic piece. Rather, we have invited Mr. David Livdahl (Columbia Law School ’77) to conclude our Symposium issue by discussing his 36-year career as a legal practitioner, including 26 years in Asia. Mr. Livdahl is a partner in the corporate practice of Paul Hastings and is currently stationed in the firm’s Beijing office. During his extensive career, Mr. Livdahl has been an influential practitioner in both China and Japan, representing major companies coming in and out of both countries. Perhaps one would find it very strange, given his roots, for Mr. Livdahl to have risen to his current position as an influential practitioner in Asia. His Minnesota college, during the years he was in school, did not offer any Asian language courses. He notes, at the time, there didn’t appear to be any benefit to learning Chinese other than to join the military or to become an academic. As such, Mr. Livdahl had to do battle with his own school’s administration to have his supplementary Chinese-language courses from other universities recognized on his transcript. He eventually was the first graduate to have a minor in Chinese (despite the fact that Chinese was not even offered at the time). Despite his roots, Mr. Livdahl found himself in the rapidly growing field of legal work in Asia. He was a key player in the founding of his firm’s Tokyo offices, and later was an important leader in the firm’s Hong Kong and Beijing offices. This article chronicles some of the ups and downs of his career. Some of the hardships were major. Many would consider a person crazy to give up a successful career and a one acre property in California to pursue work in Tokyo (an untested market at the time) and be forced to live in what any sane person would consider a very cramped apartment. However, the rewards have been greater. Mr. Livdahl accounts some of his proudest moments as an attorney in Asia, including one experience in which (perhaps exemplifying his Midwestern roots) he helped save his Japanese client’s business by calling upon the assistance of the son of an Idaho farmer. While Mr. Livdahl’s story is certainly unique, our hope is that his experiences can be educational for those considering a legal career in Asia (or considering a legal career in general).